An analysis of the anti-avoidance provision S.103 of the South African Income Tax act - Saggau, Andreas (Department of Commercial Law, 2021)
The South African Income Tax Act contains a number of specific anti-avoidance sections, as well as a general anti-avoidance section. This dissertation will focus on the general anti-avoidance section 103 of the Income Tax Act No. 58 of 1962 and highlight the individual requirements and their interpretation by the courts. Special consideration will be given to the difficulties of the normality requirement. The amendments made to the section and a brief consideration· of similar general anti-avoidance provisions in other countries shall also be evaluated. Where tax cases are analysed, it must be kept in mind that the burden of tax is imposed by Parliament in the form of the Income Tax Act or other laws while it is the Courts that apply these laws. The 'task' of the Courts has accordingly been described by Lord Templeman in the recent case of Ensign Tankers (Leasing) Ltd v Stokes: 1 'The task of the courts is to construe documents and analyse facts and to ensure the taxpayer does not pay too little tax or too, much tax but the amount of tax which is consistent with the true effect in law of the taxpayer's activities. Neither the taxpayer nor the Crown should be deprived of the fiscal consequences of the taxpayer's activities properly analysed. ' Having this '_task' in mind we will see how the general anti-avoidance provision has been enforced by the Courts. We will see if section 103 is the powerful sword in the hands of the Commissioner of Revenue or just another 'paper tiger'. Lastly I will deal with the general provision against the utilization o( assessed losses s 103(2) and dividend and interest swaps sl03 (5).